PEMBELAJARANUSHUL FIKIH BERBASIS MASALAH - Sapiudin Sapiudin (AHKAM : Jurnal Ilmu Syariah, 2014)
Learning Ushûl al-Fiqh Based on Problems. The goal of learning ushûl al-fiqhin order to apply the rules concerning useful arguments to obtain laws will appear successful if the model that is used triggers the student to think constructively and contextually by using participative learning principles in analyizing ushûl al-fiqhrules. The focus of problem that needs to be answered in this research is to see conceptually the effectiveness of learning ushûl al-fiqhbased on problems in reaching the applicable ushûl al-fiqhlearning goals. Based on conceptual-qualitative analysis results, I argue that model of problem-based learning with its various limitations can be used as an innovative model in learning ushûl al-fiqh.DOI: 10.15408/ajis.v14i2.1288